Anti-myelin-associated-glycoprotein neuropathy successfully treated with tirabrutinib. Issue 10 (October 2022) - Yasuda, Hajime; Tomizawa, Yuji; Harada, Sakiko; Sasaki, Makoto; Komatsu, Norio; Ando, Jun; Hattori, Nobutaka; Ando, Miki
Abstract: Background: Anti-myelin-associated-glycoprotein (MAG) neuropathy is a distal, predominantly demyelinating, sensory or sensory-motor polyneuropathy most often developing in the context of an IgM-type monoclonal gammopathy due to monoclonal gammopathy of undetermined significance or lymphoplasmacytic lymphoma. Rituximab is considered standard therapy for treatment naïve patients, but optimal treatment methods for relapsed/refractory patients have not been established. Case presentation: We demonstrate that tirabrutinib, a second-generation Burton kinase inhibitor, led to drastic improvements of polyneuropathy that were affirmed by nerve conduction studies in a rituximab-refractory anti-MAG neuropathy patient. Tirabrutinib continues to give excellent disease control with no apparent adverse events at 11 months since initiation, and the patient remains free of plasmapheresis sessions which were originally mandatory. Conclusion: Tirabrutinib is an extremely promising treatment option for anti-MAG neuropathy. Abstract : Anti-MAG antibody; Ibrutinib; BTK inhibitor; Lymphoplasmacytic lymphoma; IgM MGUS; Rituximab; Bruton tyrosine kinase inhibitor; Plasmapheresis; SGPG glycolipid; Sensory-motor type polyneuropathy.